MENINGKATKAN KESETIAAN PELANGGAN LEWAT CUSTOMER RELATIONSHIP MANAGEMENT - Borolla, Johanis Darwin (STIE YPPI Rembang, 2009)
AbstractThe maximization of customer satisfaction nowadays cannot be fulfill only by price strategy and product quality. Some new approaches can be implemented as a solution. One of these approaches is Customer Relationship Management (CRM). CRM used by company to increase customer satisfaction and loyalty by giving easier information accessibility and create a new relationship which is more intense and more personal, also to build customerâs trust through added more services to the customer. This idea is well-applied because it supported by information technology which can help in storing and classifying the information (data warehousing), or to track and get the data in details:economic, demography, lifestyle, physiography, and more interactive elements of the customer. Commonly, if CRM is well-applied, the information (data) of customer interaction will be recorded in details. Hence, this approach will assist the company in developing more ideas in order to give products and services which are more suitable to the customerâs needs, and the most important is to fulfill the customerâs satisfaction.Key word: Customer Relationship Management, customers satisfaction, customers loyalty